Artificial Self‐Sufficient Cytochrome P450 Containing Multiple Auxiliary Proteins Demonstrates Improved Monooxygenase Activity. Issue 12 (14th August 2018) - Haga, Tomoaki; Hirakawa, Hidehiko; Nagamune, Teruyuki
Abstract : Most bacterial cytochrome P450 monooxygenases (P450s) do not work alone because their active species is generated by two electrons supplied through two separate auxiliary proteins. Artificial "self‐sufficient" P450s, in which one molecule each of the two auxiliary proteins is arranged close to the P450s, have been developed but have not achieved the maximum catalytic turnover numbers of the P450s. In this study, the Pseudomonas putida P450 (P450cam) is assembled with multiple molecules of its auxiliary proteins, putidaredoxin (PdX) and putidaredoxin reductase (PdR), by fusion to a heterotrimeric protein. In the assembled P450cam containing one PdX and one PdR, kinetic analysis reveales that the catalytic cycle of P450cam is suspended twice awaiting the reduction of PdX by PdR. An increase in the number of PdR molecules stimulated the PdX reduction process. Assembly with two PdXs allows one PdX to be reduced during the binding of the other PdX to P450cam for the first electron transfer, eliminating one waiting step. Finally, P450cam assembled with two PdXs and three PdRs showes 92% of the maximum activity of free P450cam. Therefore, assembly with multiple molecules of auxiliary proteins will facilitate in vitro biotechnological applications of the P450s. Abstract : Bacterial cytochrome P450s (P450s) need two electrons, which are transported by ferredoxin (FdX) from ferredoxin reductase (FdR), to demonstrate their monooxygenase activities. Artificial assembly with FdX and FdR enables a bacterial P450 to work as a self‐sufficient enzyme. The catalytic cycle of the P450 assembled with one molecule of FdX is suspended twice awaiting FdX reduction by FdR. Assembly with two molecules of FdX eliminates one waiting step, and that with multiple molecules of FdR shortens the waiting time. Indeed, an assembled P450 containing two molecules of FdX and three molecules of FdR demonstrated a 1.7‐fold higher activity than that containing one molecule each of FdX and FdR. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .